QTIA, a 2.5 or 10 Gbps 4-channel array optical receiver ASIC in a 65 nm CMOS technology. (1st May 2022) - Sun, H.; Huang, X.; Chao, C.-P.; Chen, S.-W.; Deng, B.; Gong, D.; Hou, S.; Huang, G.; Kulis, S.; Li, C.-Y.; Liu, C.; Liu, T.; et al.
Abstract: The Quad transimpedance and limiting amplifier (QTIA) is a 4-channel array optical receiver ASIC, developed using a 65 nm CMOS process. It is configurable between the bit rate of 2.56 Gbps and 10 Gbps per channel. QTIA offers careful matching to both GaAs and InGaAs photodiodes. At this R&D stage, each channel has a different biasing scheme to the photodiode for optimal coupling. A charge pump is implemented in one channel to provide a higher reverse bias voltage, which is especially important to mitigate radiation effects on the photodiodes. The circuit functions of QTIA successfully passed the lab tests with GaAs photodiodes.